2018
DOI: 10.2217/fon-2018-0408
|View full text |Cite
|
Sign up to set email alerts
|

XPG Polymorphisms And Their Association With Lung Cancer Susceptibility, Overall Survival And Response In North Indian Patients Treated With Platinum-Based Doublet Chemotherapy

Abstract: Aim: The study investigates association of XPG polymorphism with lung cancer susceptibility, overall survival and clinical outcomes in North Indian population. Results: A significant protective effect was observed for 2228959 C/A polymorphism with lung cancer and its histological subtypes. An increased hazard ratio (HR) was observed in 17655 G/C variant among small-cell lung carcinoma patients with mutant genotype (HR: 2.55; p = 0.05). Individuals treated with irinotecan-cisplatin/carboplatin regimen showed a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Some studies have demonstrated that the single nucleotide polymorphisms (SNPs) of XPG may affect the development of cancer, such as lung cancer[12,13], colorectal cancer[14,15], breast cancer[16], neuroblastoma[17], Hodgkin’s lymphoma[18], and oral squamous cell carcinoma[19]. However, only a few studies have explored the associations between XPG gene SNPs and GC, and those studies show inconsistent results.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have demonstrated that the single nucleotide polymorphisms (SNPs) of XPG may affect the development of cancer, such as lung cancer[12,13], colorectal cancer[14,15], breast cancer[16], neuroblastoma[17], Hodgkin’s lymphoma[18], and oral squamous cell carcinoma[19]. However, only a few studies have explored the associations between XPG gene SNPs and GC, and those studies show inconsistent results.…”
Section: Introductionmentioning
confidence: 99%